Impact of scavenging versus predation on selected aspects of brown recluse spider, Loxosceles reclusa (Araneae:Sicariidae), biology - Ewing, Robert "JR" (Kansas State University, 2018)
The brown recluse spider (BRS), Loxosceles reclusa (Gertsch & Mulaik), receives unfavorable publicity because of its common association with humans and the medical importance of its toxic bite. BRS range includes much of the south and central United States where they can be found in almost all structures, from homes and sheds to woodpiles and discarded materials. Typical management techniques for the control of BRS involve the use of residual contact insecticides and/or the use of glue traps. Contact insecticides rely on BRS remaining in contact with a treated surface for a length of time to achieve control and may not cause significant BRS mortality. However, if the insecticide kills another household pest that the BRS later scavenges upon, and thus results in the death or decreased reproduction of the BRS, the homeowner rids themselves of pests and potentially reduces BRS populations. This research was initiated with the objective of evaluating how feeding on live vs. dead vs. insecticide-killed prey impacts selected biological aspects of BRS as indicated by, mortality, and weight change over an eight-week period. Follow-on experiments evaluated the effect on fecundity of the adult BRS surviving the eight week trials. In four trials of juvenile and five trials of adult BRS, house crickets, Acheta domesticus (Linnaeus), used as prey, were exposed to one of four treatments: 1) Spinosad insecticide treated surface, 2) synthetic pyrethroid insecticide treated surface, 3) freeze-killed and 4) an untreated (live), and fed to spiders once weekly for eight weeks. BRS exposed to synthetic pyrethroid-killed crickets had significantly greater mortality than all other treatments.
Keywords: Scavenging; Pest management; Loxosceles reclusa